Pengelolaan Laboratorium Fisika Bangunan di Jurusan Arsitektur (Analisis Kelayakan Berdasarkan ISO/IEC 17025:2017 ) - Rizki Fitria Madina; Sri Tundono; Sri Novianthi Pratiwi; Lili Kusumawati; Inavonna -; Khotijah Lahji; Fajar Rezandi (UMSU, 2023)
The Building Physics Laboratory is an educational facility that supports the quality of education. In the last 5 years, the Building Physics Laboratory at the Department of Architecture Universitas Trisakti has had the opportunity to collaborate in research activities, but does not yet have accreditation that guarantees the laboratory quality. This study was conducted to determine the condition of the building physics laboratory in the Department of Architecture at universities in Indonesia. The research results are used to prepare laboratory commercialization and laboratory development plans for the Universitas Trisakti’s Building Physics Laboratory. From this research, it is known that although the facilities and infrastructure of the Building Physics Laboratory in Universitas Trisakti are more equipped than the majority of its competitors, the condition of management and resource utilization of the Building Physics laboratory at the Department of Architecture Universitas Trisakti needs improvement if they want to get ISO 17025:2017 accreditation.